Impacts of climate change on water resources in the Huong River basin and adaptation measures - Thuc, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 4, 2010)
Abstract. This study investigates impacts of climate change on water resource in the Huong River basin in the Central Vietnam. Hydrological responses of six climate change scenarios were calculated. Results reveal that climate change would cause significant increase in rainfall in wet season resulting in an increase in river flow. By contrast, the decreasing trend of river flow in dry season is a consequence of the decline of rainfall and increase of evapoưanspiration under most scenarios. Sea level rise coupled with the lowering of river stages may exacerbate salinity intrusion. Impacts of climate change on socio-economic sectors such as agriculture, tourism, biodiversity, fishery and aquaculture are assessed, and adaptation options for Thua Thien - Hue Province are proposed. Keywords: climate change, water resources, hydrological model, flood, adaptation.